Virtual Reality Analgesia for Children With Large Severe Burn Wounds During Burn Wound Debridement - Hoffman, Hunter G.; Patterson, David R.; Rodriguez, Robert A.; Peña, Raquel; Beck, Wanda; Meyer, Walter J. (Frontiers in Virtual Reality, 2020)
The objective of this study was to compare the effect of adjunctive virtual reality vs. standard analgesic pain medications during burn wound cleaning/debridement. Participants were predominantly Hispanic children aged 6–17 years of age, with large severe burn injuries (TBSA = 44%) reporting moderate or higher baseline pain during burn wound care. Using a randomized between-groups design, participants were randomly assigned to one of two groups, (a) the Control Group = pain medications only or (b) the VR Group = pain medications + virtual reality. A total of 50 children (88% Hispanic) with large severe burns (mean TBSA > 10%) received severe burn wound cleaning sessions. For the primary outcome measure of worst pain (intensity) on Study Day 1, using a between groups ANOVA, burn injured children in the group that received virtual reality during wound care showed significantly less pain intensity than the No VR control group, [mean worst pain ratings for the No VR group = 7.46 (SD = 2.93) vs. 5.54 (SD = 3.56), F(1,48) = 4.29, < 0.05, MSE = 46.00]. Similarly, one of the secondary pain measures, “lowest pain during wound care” was significantly lower in the VR group, No VR = 4.29 (SD = 3.75) vs. 1.68 (2.04) for the VR group, F(1,47) = 9.29, <0.005, MSE = 83.52 for Study Day 1. The other secondary pain measures showed the predicted pattern on Study Day 1, but were non-significant. Regarding whether VR reduced pain beyond Study Day 1, absolute change in pain intensity (analgesia = baseline pain minus the mean of the worst pain scores on Study days 1–10) was significantly greater for the VR group, F(1,48) = 4.88, p < 0.05, MSE = 34.26, partial eta squared = 0.09, but contrary to predictions, absolute change scores were non-significant for all secondary measures.